RANCANGAN E-COMMERCE DAN PAYMENT API MIDTRANS UNTUK PRODUK UMKM (STUDI KASUS PADA RUMAH KEMASAN) - Edy Nasri; Ely Nuryani; Nanang Agustiawan (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
In the process of product marketing micro, small and medium enterprises on Shop Rumah Kemasan Pandeglang, still being done by marketing the product through the storefront and the goods are stored in the warehouse so that the search, counting of goods directly gets to the warehouse and recording is still using bookkeeping so that the service process for goods is slow, it often happens that goods are not found resulting in data loss, it is necessary to have a system that manages the transaction process for data collection and online sales in order to increase the number of sales and minimize data loss. The system that will be designed later is the e-commerce and payment API midtrans, this research was conducted to increase sales of micro, small and medium business products by providing a system that can be accessed by everyone anywhere and anytime so that in the system that will be built later, buyers no longer need to wait long to buy products and for payments there is no need to make cash payments just online, and for product sellers can speed up the sales process, organized data management. In the design and development stage of e-commerce applications, researchers use the Extreme Programming method, modeling using the UML which produces a software that is expected, and the language used in this development is the PHP programming language, the MySQL database and for payments based on the Midtrans payment gateway application programming interface.